Reported Speech as a Supraphrasal Unity - Kostanyan, Zara (Armenian Folia Anglistika, 2009)
The analysis of supraphrasal indirect speech reveals that the paradigm of the given syntactic unit in the language system is formed in accordance with its structural-semantic characteristics which make it possible to distinguish it in the flow of speech. The lexical, grammatical, tense and stylistic factors prove to be important in the distinction of the supraphrasal indirect speech.